2019
DOI: 10.1002/ijfe.1799
|View full text |Cite
|
Sign up to set email alerts
|

The intertwining of credit and banking fragility

Abstract: Although the literature has provided evidence of the predictive power of credit for financial and banking crises, this article aims to investigate the grounds of this link by assessing the interrelationships between credit and banking fragility. The main identification assumption represents credit and banking fragility as a system of simultaneous joint data generating processes whose error terms are correlated. We test the null hypotheses that credit positively affects banking fragility-a vulnerability effect-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…This kind of interrelationship between private credit and non-performing loans on economic performance extends the intertwining effects evidenced in Creel et al (2019). There, we show that higher private credit generates higher ratios of non-performing loans -a vulnerability effect -and that higher ratios of non-performing loans generate a decline in private credit -a trauma effect -.…”
Section: Baselinesupporting
confidence: 77%
“…This kind of interrelationship between private credit and non-performing loans on economic performance extends the intertwining effects evidenced in Creel et al (2019). There, we show that higher private credit generates higher ratios of non-performing loans -a vulnerability effect -and that higher ratios of non-performing loans generate a decline in private credit -a trauma effect -.…”
Section: Baselinesupporting
confidence: 77%
“…Other studies have focused on banking activities. Creel et al (2021) studied a panel of EU countries over the period 1998-2012 and found a positive effect of credit on bank fragility in the euro area but not in the periphery of the EU. They also found a negative effect of bank fragility on lending for the EU as a whole.…”
Section: Literature Review Of Crisis Results Over the Banking Systemsmentioning
confidence: 99%
“…It is useful to frame this relationship for EMCCA. In this perspective, Creel et al (2016) work on a sample of European Union countries (27 countries) over the period 1998-2011 and use the generalised method of moments. Creel et al (2016) find that the policy space of the central bank expands in the presence of prudential policy instruments.…”
Section: Theory and Empirical Approachesmentioning
confidence: 99%
“…In this perspective, Creel et al (2016) work on a sample of European Union countries (27 countries) over the period 1998-2011 and use the generalised method of moments. Creel et al (2016) find that the policy space of the central bank expands in the presence of prudential policy instruments. However, the introduction of prudential policy tools into the relationship does not allow the authors to conclude whether an inverse relationship between financial sector development and inflation is ruled out.…”
Section: Theory and Empirical Approachesmentioning
confidence: 99%